Implementation of Literacy Games Word Cards in Overcoming Reading Difficulties in Grade 1 Primary School Students - Agustina Putri Candra Dewi; Honest Ummi Kaltsum (Journal of Educational Sciences, 2026)
Preliminary studies indicate that lower grade students still experience difficulties in reading, such as recognising letters, sounds, and vocabulary, including at SD Muhammadiyah 3 Pekajangan. This study aims to describe the planning and implementation of the Word Card Literacy Game and its effectiveness in improving the reading skills of first-grade students. The method used is descriptive qualitative with data collection through observation, interviews, and documentation. The data were analysed based on the themes of planning, implementation, evaluation, and student responses, with data validity tested through triangulation and member checks. The results showed that the use of the Word Card Literacy Game increased students' enthusiasm, participation, and ability to recognise letters, spell, compose words, and understand vocabulary. Visual media and game activities proved to be effective in creating more engaging and interactive learning. The Word Card Literacy Game can be used as an alternative strategy to improve the reading skills of primary school students.